Breastfeeding friendly airport to support healthy tourism - Lina Handayani; Arzani Arzani; Mahayu Agustia Jayanti; Rini Puji Astuti; Della Noviyanti; Maya Kusuma Dewi (International Journal of Public Health Science (IJPHS), 2019)
Motivation for breastfeeding and social support is very important for the success of exclusive breastfeeding. Breastfeeding support and motivation is obtained from family, leaders and the government. The implication of the government support given is the existence of regulations for organizer of public facilities that stating that the owner of public facilities must support the exclusive breastfeeding program at the airport. The airport is an important means for the mobility of both domestic and foreign tourist. The role of airport is very important to realizing healthy tourism. This study used a case study design. The subjects of this study were the leaders, staff and visitors of Adisutjipto International Airport. The number of informants is five people. The research instruments were interview guides and observation forms. Knowledge, attitudes and informant support for the exclusive breastfeeding program are good. There needs to be a stronger promotion effort for all levels of society so that exclusive breastfeeding programs can be achieved. Provision of nursery rooms at Adisutjipto International Airport is in accordance with government standards with facilities such as tables, chairs, baby boxes, washing stand, dispensers and trash can. Adisutjipto International Airport is confirmed as a breastfeeding friendly airport.